A urdidura espacial do capital e do trabalho no cerrado do sudoeste goiano - Mendonça, Marcelo Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
As transformações espaciais, decorrentes das mudanças aceleradas pela reestruturação produtiva do capital, promoveram uma efervescência política no campo brasileiro, propiciando uma agudização das contradições e redefinindo a gestão societária do capital e do trabalho. A retomada dos movimentos sociais na luta pela terra significa a possibilidade de milhares de famílias desterritorializadas de se reterritorializar na efetiva realização da reforma agrária. A estratégia do capital se concretiza em novas formas de controle social, mas as alterações no conteúdo das classes sociais forjadas no enfrentamento do capital e do trabalho, implicam em novas (re)arrumações espaciais, produto-produtor da contradição viva e, portanto, condição potencial para a emancipação social. A pesquisa está centrada na geografia do trabalho – a essência do Homem – a hominização criadora e potenciadora das ações humanas rumo à emancipação social – sendo tratada não enquanto uma nova corrente do pensamento geográfico, mas enquanto um “outro olhar” sobre a realidade social, enxergando “por dentro” as contradições, as clivagens e as fraturas a partir da territorialização do capital e do trabalho no Cerrado do Sudeste Goiano. A relação com o meio-ambiente sofre brusca alteração, principalmente nas áreas de chapadas, até então pouco “aproveitadas”, pois apresentavam solos pouco férteis para cultivos intensivos e excesso de água no período chuvoso, o que dificultava as atividades agrícolas. Os chegantes, portadores do “progresso”, utilizam o aparato técnico e tecnológico disponível, mediante a disponibilização de pesquisas científicas...

The spatial transformations, caused by the fast changes in the reestructuring of the capital have promoted a political effervescence in the Brazilian country, permiting increasing the contradictions, redefining the social movements in the fight for land. Means the possibility of thousands of landless families, that had their dignity stolen of restabilish themselves in an effective land reform. The capital’s strategy that becomes effective in new forms of social control, due to the changes in content of social class, forged, in the facing of capital and work, this implies in new spatial (re) arrangements, product-producer of the living contradiction and, therefore, condition to a social emancipation. The theme’s relevance – work for the Geographical science is treated not as a new trend of the Geographical thought, but as an – ‘other look’ on the social reality, seeing ‘inside’ the contradiction, founded in the relation capital x work. The work as founding, – the men’s essence – the humanization creator and potential of human action towards the social emancipation. The relation with the environment suffers abbupt change, mainly in the areas of plateau, until now, rarely used, because presented a not so fertile soil for intensive cultivation and execive water during the raining season, what made it difficult for agricultural activities. The newcomers, helders of ‘progress’, used the available technical and technological apparatus, face to the disponibilization of scientific researches, promoting the transformation of areas untill now almost unproductive in to agricultural granary. The social and environmental cost of modernization of agriculture in areas of scrub land (Cerrado) specifically at the goianos, south east plateau. The productive restructuring of capital and the ‘re-invention’ of the social reations submitted to the ruling of the market... (Complete abstract click electronic address below)
Keywords: Camponeses; Movimentos sociais rurais; Cerrados; Geografia do trabalho; Camponeses e trabalhadores da terra; Social movements